Development Of Philosophy Of Science In Management In The Digital Era - Ningsih, Supiah; Yusnandar, Willy; Sipahutar, Muhammad Ali; Mujiatun, Siti (Jurnal Ekonomi, 2024)
Revolutions in science and technology have occurred many times, with great and unexpected consequences. Philosophy is the mother of all sciences that develop in the world, philosophy plays an important role in every development of science. Management philosophy is a collection of knowledge and beliefs that provide a broad basis or basis for determining problem solving. This study uses a literature study research method. One type of research is called library research and involves various text reference materials to see which ones are still relevant to this problem. Documentation techniques will be used as a collection method for this final assignment. Researchers collect various sources and key notes that are still relevant to the problem as part of the documentation process, which in itself is a method used by researchers. Using this approach makes it much easier to obtain accurate and complete data. The four perspectives of epistemological and ontological formations provide a framework for management to know how they act as managers of an organization. The industrial revolution 4.0 will also have an impact on changing lifestyles and community habits. For companies that cannot respond to the impact of these changes, they will be crushed by themselves. Thus, human resource management in an organization/company needs to design a program that can align the need to achieve organizational/business goals with the existence of its human resources.